Fibrin Clot–Augmented Meniscal Repair - Tebourbi Anis MD; Triki Rami MD; Nefiss Mouadh MD; Mohamed Amine Gharbi MD; Bouzidi Ramzi MD (Video Journal of Sports Medicine)
Background: Failure rate of meniscal repair can reach 25%. Multiple techniques have been used to increase meniscal healing, notably biological augmentation techniques. One of them is fibrin clot–augmented meniscal repair, which will be described in this video. Indications: This technique is indicated mainly for the lesions with a high failure rate. This includes large, horizontal, and radial tears and even for meniscal cysts, especially in a stable knee. This technique can also be used in revision meniscal suture when failure is no longer an option. Surgical Technique: Fibrin clot is prepared from sterile peripheral venous blood from the patient. A plastic syringe is used to stir the blood in a sterile glass container. The fibrin clot is then formed and washed rigorously with saline solution. Rolling the fibrin clot which is fixed to the syringe allows to give the fibrillar aspect of the clot. The formed fibrin clot is now solid enough to be manipulated and can be fixed to a vicryl suture thread allowing it to enter the knee and be fixed inside the meniscal lesion. The clot is wrapped inside the meniscal lesion with inside-out or outside-in suture technique. Results: We used this technique for multiple types of lesions, like bucket handle meniscal tear, horizontal meniscal cleavage, parrot beak tear, and even in lesions within white-white zone. The postoperative protocol is the same as standard inside-out meniscal repair. This technique has been used in the literature with promising results. Conclusion: The fibrin clot–augmented meniscal repair is a demanding but promising technique. We need further follow-up to confirm its effectiveness. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.